The c.3274T> C mutation in the CFTR gene results in bronchiectasis and loss of lung function in a 44-year-old Peruvian woman: A very rare condition - Pecho-Silva, Samuel (2021)
CF is an autosomal recessive disease, requiring mutations to be present in both alleles in the CF transmembrane conductance regulatory gene (CFTR). The c.3274T> C (p.Tyr1092His) mutation is not registered in the “CFTR2 project” database, but it is registered in The Human Gene Mutation Database. Neither are the two DNAAF4 c.1177C> T (p.Leu393Phe) and DNAAF5 c.1195G> A (p.Glu399Lys) mutations found in the "CFTR Project”, and their clinical consequences are currently uncertain. Here, we report the case of a Peruvian woman presenting this mutation, bronchiectasis and loss of lung function and provide a review of the literature.